THE THREAT OF UNDERWATER DRONES IN INDONESIAN WATERS TERRITORY - Hariadi, Imam (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2023)
Along with the development of the strategic environment in the Indo-Pacific, conflict escalation has occurred at several points in this area. And Indonesia, as one of the countries in the Indo-Pacific Region, is also affected by this condition. One of the leading weapons currently used by regional countries today is underwater drones. As an increasingly popular advanced technology, undersea drones provide the potential for their use in various applications, including marine resource exploration, underwater environmental surveys, and military. However, these technological advances also threaten the security and sustainability of Indonesia's territorial waters. This research aims to identify potential threats arising from using underwater drones, both from national security and its impact on the marine environment. The results of this research show that the illegal use of underwater drones is very detrimental to coastal states, so coastal states must immediately take legal and diplomatic steps to prevent territorial violations carried out by using unmanned vehicles entering Indonesian waters. . Undersea drones also have the potential to be used in espionage, weapons smuggling, and sabotage of underwater infrastructure. Hopefully, this research can provide a deeper understanding of the threat of underwater drones and provide input for the authorities in developing policies and strategies to protect the security and sustainability of Indonesia's territorial waters from this potential threat. Keywords: Threats, Undersea Drones, Indonesian Waters